La responsabilidad civil derivada de la violencia económica de género dentro del matrimonio - Anchali Chacón, Nayeli Melissa (2025)
This academic article addresses and analyzes the civil liability arising from gender-based economic violence, developing its manifestations in marriage and effects on the victim from which it is obtained that indeed the actions of abuse fail to meet the obligations under the marriage contract, and also generates damage, which, therefore, will be the task of the jurist, identify the causal link between the damage and the conduct of the aggressor, along with the other elements of civil liability to demand monetary and comprehensive reparation for the victim. Through a synthetic analytical methodology and bibliographic technique, it has become evident that there is a great deficiency in Ecuadorian regulations that guarantee the rights of women victims of economic violence in marriage.